Menstrual Cycle Phases Influence on Cardiorespiratory Response to Exercise in Endurance-Trained Females - Rael, Beatriz (Int J Environ Res Public Health, 2021)
The aim of this study was to analyse the impact of sex hormone fluctuations throughout the menstrual cycle on cardiorespiratory response to high-intensity interval exercise in athletes. Twenty-one eumenorrheic endurance-trained females performed an interval running protocol in three menstrual cycle phases: early-follicular phase (EFP), late-follicular phase (LFP) and mid-luteal phase (MLP). It consisted of 8 × 3-min bouts at 85% of their maximal aerobic speed with 90-s recovery at 30% of their maximal aerobic speed. To verify menstrual cycle phase, we applied a three-step method: calendar-based counting, urinary luteinizing hormone measurement and serum hormone analysis. Mixed-linear model for repeated measures showed menstrual cycle impact on ventilatory (EFP: 78.61 ± 11.09; LFP: 76.45 ± 11.37; MLP: 78.59 ± 13.43) and heart rate (EFP: 167.29 ± 11.44; LFP: 169.89 ± 10.62; MLP: 169.89 ± 11.35) response to high-intensity interval exercise (F(2.59) = 4.300; p = 0.018 and F(2.61) = 4.648; p = 0.013, respectively). Oxygen consumption, carbon dioxide production, respiratory exchange ratio, breathing frequency, energy expenditure, relative perceived exertion and perceived readiness were unaltered by menstrual cycle phase. Most of the cardiorespiratory variables measured appear to be impassive by menstrual cycle phases throughout a high-intensity interval exercise in endurance-trained athletes. It seems that sex hormone fluctuations throughout the menstrual cycle are not high enough to disrupt tissues’ adjustments caused by the high-intensity exercise. Nevertheless, HR based training programs should consider menstrual cycle phase.